Combined off‐pump coronary bypass grafting without heparin and liver transplantation: A novel approach to a complex dilemma. Issue 2 (15th November 2019) - Brozzi, Nicolas A.; Beduschi, Thiago; Salerno, Tomas; Cifuentes, Renzo; Ghodsizad, Ali; Martin, Eric; Vianna, Rodrigo; Loebe, Matthias
Abstract: Cardiac disease is a leading cause of early mortality for patients undergoing liver transplantation (LT), and severe coronary artery disease (CAD) is usually considered a contraindication for LT in patients with cirrhosis. Incidence of CAD in LT candidates has increased in recent years. While stable patients might be candidates for percutaneous interventions, patients with decompensated liver failure, or critical coronary lesions present a therapeutic challenge, and are often not considered candidates for LT. We present the case of a 60 year old male patient with decompensated liver failure, and critical CAD, who received successful combined off‐pump coronary bypass grafting without heparin and LT using ex vivo normothermic liver perfusion machine. This approach represents a novel strategy to offer LT to this very selective group of patients.